Cloning and characterizing cDNA sequences coding high-mannose n-glycan binding lectins from cultivated red algae Eucheuma denticulatum and Kappaphycus striatum - Hung, Le Dinh; Hirayama, Makoto; Hori, Kanji (Vietnam Journal of Biotechnology, 2016)
The red algae, Eucheuma denticulatum and Kappaphycus striatum have been widely cultivated in Vietnam as a source of carrageenophytes for industry. In the past, biochemical properties of lectins isolated from these algae has been characterized and evaluated extensively. However, gene coding for such lectins isn’t studied yet. In this study, their full length cDNA is amfplified using cDNA ends (RACE) methods. Sequence analysis revealed that cDNA of EDA-2 from E. denticulatum consisted of 1,158 bp containing 103 bp of a 5’untranslated region, 248 bp of 3’untranslated region, and 807 bp of an open reading frame; and cDNA of KSA-2 from K. striatum consisted of 1174 bp containing 94 bp of the 5’-untranslated region, 273 bp of 3’untranslated region and 807 bp of the open reading frame. The cDNA of both EDA-2 and KSA-2 encoded for a polypeptide of 269 amino acids including an initiating methionine, but differed in sequences and molecular masses. The deduced amino acid sequences of EDA-2 and KSA-2 composed of four tandem repeated domains with about 67 amino acids each. The primary structure of EDA-2 and KSA-2 is highly similar to those of the high mannose N-glycan specific lectins including OAA from cyanobacterium, BOA, MBHA and PFA from bacteria, and ESA-2, KAA-1, KAA-2 from macro red algae, which showed strong anti-HIV and anti-influenza virus activities. These results indicate that these cultivated algae are becoming promising materials for production of anti-virus reagent or functional food that can prevent virus infection in future.